A degradable and environmentally friendly straw and preparation method thereof
By using modified thermoplastic starch and polylactic acid in the straw material, the problem of insufficient mechanical properties and water resistance stability of existing materials is solved, and the high strength and toughness and good biodegradability of the straw material are achieved.
Patent Information
- Application Number
- CN202410768190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The existing degradable straw materials have shortcomings in terms of mechanical properties and water resistance stability, and the compatibility between starch and polylactic acid is insufficient, resulting in deterioration of the mechanical properties of the material and high water absorption and swelling.
Modified thermoplastic starch is used as dopant material, and highly reactive acrylic anhydride reacts with tapioca starch molecules, introduces alkenyl modification, and free radicals are generated by γ irradiation, promoting the addition of modifiers and starch molecules to form modified thermoplastic starch. The modified starch is eutectic and mixed with the polylactic acid matrix to reduce the influence of starch on the mechanical properties of the polylactic acid matrix, and strengthen the composite material through the interaction of the polyester structure with the calcium carbonate filler.
The excellent mechanical properties and water resistance stability of the straw material are achieved, the water absorption and swelling loss of starch is reduced, the stability of the straw structure is maintained, and the good biodegradability is achieved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of degradable composite materials, and in particular, relates to a degradable and environment-friendly straw and a preparation method thereof. Background Art
[0002] Straws are used to drink various beverages. They greatly facilitate people's daily diet and life and have become an indispensable item in daily life. Traditional straws are made of metal, plastic, rubber, etc. Among them, polyolefin straws are low-cost and easy to carry and are widely used. However, these polyolefin materials are difficult to degrade and have become an important source of white pollution. At present, some industries have banned the use of non-degradable straws.
[0003] Degradable materials refer to materials that can be completely degraded into carbon dioxide, water and other environmentally friendly and non-toxic substances through physical, chemical and microbial effects in a natural environment or under specific conditions. At present, the degradable materials used in straw materials are mainly polylactic acid, which has a wide range of sources and can be completely degraded. However, pure polylactic acid materials are more brittle and have a higher preparation cost than polyolefin materials. In the prior art, starch doping can achieve a certain toughening effect, maintain good biodegradability and high biosafety. However, starch and polylactic acid are not compatible enough, and the doping amount reaching a certain proportion will cause the mechanical properties of the material to deteriorate sharply. In addition, starch has high water absorption and swelling properties, and it is easy to absorb water during use, resulting in insufficient stability of the straw. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a degradable and environmentally friendly straw and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A degradable and environment-friendly straw comprises, by weight percentage, 26-35 wt% of modified thermoplastic starch, 2.8-3.3 wt% of a compatibilizer and 12-17 wt% of calcium carbonate micropowder, with the remainder being polylactic acid.
[0007] The modified thermoplastic starch is prepared by the following method:
[0008] Step A1: premix acrylic anhydride and cyclohexane under dry nitrogen protection, add cassava starch and mix, heat to 50-60° C., stir at 40-60 rpm to react for 2.5-3 hours, add ammonia water for washing after the reaction, let stand and precipitate to remove the liquid phase, and then vacuum dry to obtain olefinated starch;
[0009] Furthermore, the usage ratio of cassava starch, acrylic anhydride and cyclohexane is 50g:60-80mmol:55-70mL, and acrylic anhydride reacts with hydroxyl groups in cassava starch molecules to introduce olefinic modification and improve the reactivity of starch molecules.
[0010] Step A2: Mix epoxidized soybean oil, chitosan quaternary ammonium salt and ethyl acetate, control the temperature in a water bath to 30-40° C., apply stirring at 90-120 rpm, slowly add mercaptoethylamine, and control the total reaction time of mercaptoethylamine addition to be 4-5 hours. After the reaction is completed, vacuum dry to remove ethyl acetate to obtain a modifier;
[0011] Furthermore, the usage ratio of the epoxy amount of the epoxidized soybean oil, mercaptoethylamine, chitosan quaternary ammonium salt and ethyl acetate is 0.1 mol: 70-80 mmol: 20-25 mg: 120-150 mL, and the active amino group of the mercaptoethylamine is ring-opened with the epoxy group on the epoxidized soybean oil chain.
[0012] Step A3: mixing the olefinated starch, the modifier and ethanol, subjecting the mixture to gamma irradiation treatment, controlling the irradiation dose to 80-100 kGy, and vacuum drying to remove the ethanol after the irradiation to obtain modified thermoplastic starch;
[0013] Furthermore, the usage ratio of olefinic starch, modifier and ethanol is 50g:4.2-5.5g:65-75mL, and under high-energy irradiation, the starch molecules generate free radicals, which promote the addition of active thiol groups in the modifier to the olefinic groups introduced on the starch molecules, so as to graft the modifier onto the starch molecules;
[0014] Furthermore, the gamma irradiation is carried out with a Co-60 irradiation source, and the irradiation dose rate is 150-200 Gy / min.
[0015] Furthermore, the compatibilizer is selected from polyglycerol stearate, preferably polyglycerol decastearate.
[0016] A method for preparing a degradable and environmentally friendly straw comprises the following steps:
[0017] Step S1: Mix the raw materials according to the proportion, mix them evenly with a high-speed mixer, add them into a torque rheometer for internal kneading and blending, cool and crush the discharged materials to obtain a composite masterbatch;
[0018] Step S2: melt-extrude the composite masterbatch using an extruder, and cut it after cooling to obtain a degradable and environmentally friendly straw.
[0019] Furthermore, the temperature of the banburying blending is 170±5° C., and the banburying blending time is 12-16 min.
[0020] Furthermore, during the melt extrusion process, the temperature zones are set as: zone one 155-170°C, zone two 165-180°C, zone three 180-195°C, zone four 185-195°C, zone five 190-200°C, zone six 180-190°C, and the die temperature is 190-200°C.
[0021] Beneficial effects of the present invention:
[0022] The degradable and environment-friendly straw disclosed by the invention uses polylactic acid as a base material and is doped with a self-made modified thermoplastic starch, so that the straw material has excellent mechanical properties and water-resistant stability; the modified thermoplastic starch uses cassava starch as a raw material, and highly reactive acrylic anhydride reacts with hydroxyl groups in cassava starch molecules to introduce olefinic modification, thereby improving the reactivity of starch molecules, namely, preparing olefinic starch; the active amino groups of mercaptoethylamine and epoxy groups on epoxy soybean oil chains are ring-opened to introduce thiol modification, namely, preparing a modifier; and then γ-irradiation is used to make the starch molecules generate free radicals, thereby promoting the addition of active thiol groups in the modifier with olefinic groups introduced on the starch molecules, thereby grafting the modifier onto the starch molecules, namely, preparing the modified thermoplastic starch; the modified thermoplastic starch uses starch molecular chains as a core material, and the surface is modified by the modified The agent introduces a polyester structure to reduce the hydrogen bond content between starch molecules. At the same time, the polyester structure serves as a hot-melt adhesive material, which makes the starch have a certain thermoplasticity. The polyester structure has good compatibility with the polylactic acid matrix and can be fully eutectic mixed with the polylactic acid matrix during the melt blending process, thereby reducing the influence of starch on the mechanical properties of the polylactic acid matrix. In addition, the sulfur-nitrogen organic structure introduced by mercaptoethylamine modification forms a chelating effect, which interacts with the added calcium carbonate filler to strengthen the composite material, so that the straw material has excellent mechanical properties, which is beneficial to maintaining the stability of the straw structure during use. In addition, the polyester structure itself has a certain hydrophobicity, while reducing the hydroxyl content in the starch molecules, reducing the water absorption and swelling loss of the starch molecules, and maintaining the stability of the straw structure and use. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] 1. Preparation of modified thermoplastic starch
[0026] Step A1: premix acrylic anhydride and cyclohexane under the protection of dry nitrogen, add cassava starch and mix, heat to 60°C, and stir at 60rpm to react for 2.5h, wherein the amount ratio of cassava starch, acrylic anhydride and cyclohexane is 50g:80mmol:70mL, and after the reaction, add 7wt% of ammonia water by mass of the reaction liquid for washing, and during the implementation process, use 10% diluted ammonia water by mass, let stand for 24h to precipitate, remove the liquid phase and vacuum dry to obtain olefinated starch.
[0027] Step A2: Mix epoxidized soybean oil, chitosan quaternary ammonium salt and ethyl acetate, control the temperature of the water bath to 40°C, apply stirring at 120rpm, then slowly add mercaptoethylamine, control the addition time to 1.5h, continue to stir the reaction at constant temperature after complete addition, and control the total addition reaction time of mercaptoethylamine to 4h, wherein the epoxy amount of the epoxidized soybean oil, mercaptoethylamine, chitosan quaternary ammonium salt and ethyl acetate are used in a ratio of 0.1mol:80mmol:25mg:150mL. During the implementation process, the epoxidized soybean oil uses the ESO-KLO3 raw material provided by Zibo Kailian Chemical Co., Ltd., and the chitosan quaternary ammonium salt uses the hydroxypropyltrimethylammonium chloride chitosan of Shandong Fengtai Biotechnology Co., Ltd.; after the reaction is completed, vacuum drying is performed to remove ethyl acetate to obtain a modifier.
[0028] Step A3: Take olefinated starch, modifier and ethanol and mix them evenly, then transfer the mixture into an irradiation kettle, use Co-60 as the irradiation source for gamma irradiation, control the irradiation dose rate to 200 Gy / min, and the irradiation dose to 100 kGy, wherein the amount ratio of olefinated starch, modifier and ethanol is 50 g:5.5 g:75 mL, and after the irradiation, vacuum drying is performed to remove ethanol to obtain modified thermoplastic starch.
[0029] 2. Preparation of degradable and environmentally friendly straws
[0030] Step S1: Take the raw materials according to weight percentage, polylactic acid 54.2wt%, NatureWorks 4032D raw material is used in the implementation process; modified thermoplastic starch 26wt%, self-made in this embodiment; compatibilizer 2.8wt%, Shandong Binzhou Jinsheng New Materials Technology Co., Ltd.'s ten polyglycerol ten stearate is used in the implementation process; calcium carbonate micropowder 17wt%, Hubei Tongji Furao Calcium Resources Development Co., Ltd.'s 1250 mesh food-grade calcium carbonate is used in the implementation process; each raw material is mixed according to the proportion, added into a high-speed mixer and mixed at 800rpm for 10min, and then transferred to a torque rheometer, the temperature is controlled at 170±5°C, and the mixing is carried out for 16min. The torque tends to be stable, the material is cooled and crushed to obtain a composite masterbatch.
[0031] Step S2: melt-extrude the composite masterbatch using an extruder, wherein the temperature zones during the melt extrusion process are set as: 170°C for zone one, 180°C for zone two, 195°C for zone three, 195°C for zone four, 200°C for zone five, 1190°C for zone six, and the die temperature is 200°C. After cooling, cut to obtain degradable and environmentally friendly straws.
[0032] Example 2
[0033] 1. Preparation of modified thermoplastic starch
[0034] Step A1: premix acrylic anhydride and cyclohexane under the protection of dry nitrogen, add cassava starch and mix, heat to 50°C, and stir at 40rpm for 3h, wherein the amount ratio of cassava starch, acrylic anhydride and cyclohexane is 50g:60mmol:55mL, and after the reaction, add 5wt% of ammonia water by mass of the reaction liquid for washing, and during the implementation process, use 10% diluted ammonia water by mass, let it stand for 24h to precipitate, remove the liquid phase and vacuum dry to obtain olefinated starch.
[0035] Step A2: Mix epoxidized soybean oil, chitosan quaternary ammonium salt and ethyl acetate, control the temperature of the water bath to 30°C, apply 90rpm stirring, then slowly add mercaptoethylamine, control the addition time to 2h, continue to stir the reaction at constant temperature after complete addition, and control the total addition reaction time of mercaptoethylamine to 5h, wherein the epoxy amount of the epoxidized soybean oil, mercaptoethylamine, chitosan quaternary ammonium salt and ethyl acetate are used in a ratio of 0.1mol:70mmol:20mg:120mL. During the implementation process, the epoxidized soybean oil uses the ESO-KLO3 raw material provided by Zibo Kailian Chemical Co., Ltd., and the chitosan quaternary ammonium salt uses the hydroxypropyltrimethylammonium chloride chitosan of Shandong Fengtai Biotechnology Co., Ltd.; after the reaction is completed, vacuum drying is performed to remove ethyl acetate to obtain a modifier.
[0036] Step A3: Take the olefinic starch, the modifier and ethanol and mix them evenly, then transfer the mixture into an irradiation kettle, use Co-60 as the irradiation source for gamma irradiation, control the irradiation dose rate to 150 Gy / min, and the irradiation dose to 80 kGy, wherein the amount ratio of the olefinic starch, the modifier and the ethanol is 50 g:4.2 g:65 mL, and after the irradiation, vacuum drying is performed to remove the ethanol to obtain modified thermoplastic starch.
[0037] 2. Preparation of degradable and environmentally friendly straws
[0038] Step S1: Take the raw materials according to weight percentage, polylactic acid 49.7wt%, NatureWorks 4032D raw material is used in the implementation process; modified thermoplastic starch 35wt%, self-made in this embodiment; compatibilizer 3.3wt%, Shandong Binzhou Jinsheng New Materials Technology Co., Ltd.'s ten polyglycerol ten stearate is used in the implementation process; calcium carbonate micropowder 12wt%, Hubei Tongji Furao Calcium Resources Development Co., Ltd.'s 1250 mesh food-grade calcium carbonate is used in the implementation process; each raw material is mixed according to the proportion, added into a high-speed mixer and mixed at 800rpm for 10min, and then transferred to a torque rheometer, the temperature is controlled at 170±5°C, and the mixing is carried out for 12min. The torque tends to be stable, the material is cooled and crushed to obtain a composite masterbatch.
[0039] Step S2: melt-extrude the composite masterbatch using an extruder, wherein the temperature zones during the melt extrusion process are set to: 155°C for zone one, 165°C for zone two, 180°C for zone three, 185°C for zone four, 190°C for zone five, 180°C for zone six, the die temperature is 190°C, and cut after cooling to obtain degradable and environmentally friendly straws.
[0040] Example 3
[0041] 1. Preparation of modified thermoplastic starch
[0042] Step A1: premix acrylic anhydride and cyclohexane under the protection of dry nitrogen, add cassava starch and mix, heat to 55°C, and stir at 60rpm for 2.8h, wherein the amount ratio of cassava starch, acrylic anhydride and cyclohexane is 50g:70mmol:65mL, and after the reaction, add 7wt% of ammonia water by mass of the reaction liquid for washing, and during the implementation process, use 10% diluted ammonia water by mass, let stand for 24h to precipitate, remove the liquid phase and vacuum dry to obtain olefinated starch.
[0043] Step A2: Mix epoxidized soybean oil, chitosan quaternary ammonium salt and ethyl acetate, control the temperature of the water bath to 32°C, apply stirring at 120rpm, then slowly add mercaptoethylamine, control the addition time to 1.7h, continue to stir the reaction at constant temperature after complete addition, and control the total addition reaction time of mercaptoethylamine to 4.5h, wherein the epoxy amount of the epoxidized soybean oil, mercaptoethylamine, chitosan quaternary ammonium salt and ethyl acetate are used in a ratio of 0.1mol:80mmol:22mg:130mL. During the implementation process, the epoxidized soybean oil uses the ESO-KLO3 raw material provided by Zibo Kailian Chemical Co., Ltd., and the chitosan quaternary ammonium salt uses the hydroxypropyltrimethylammonium chloride chitosan of Shandong Fengtai Biotechnology Co., Ltd.; after the reaction is completed, vacuum drying is performed to remove ethyl acetate to obtain a modifier.
[0044] Step A3: Take the olefinic starch, the modifier and ethanol and mix them evenly. Then transfer the mixture into an irradiation kettle and use Co-60 as the irradiation source for gamma irradiation. The irradiation dose rate is controlled to be 180 Gy / min and the irradiation dose is 95 kGy. The amount ratio of the olefinic starch, the modifier and the ethanol is 50 g:5 g:70 mL. After the irradiation, vacuum drying is performed to remove the ethanol to obtain modified thermoplastic starch.
[0045] 2. Preparation of degradable and environmentally friendly straws
[0046] Step S1: Take the raw materials according to weight percentage, polylactic acid 49.9wt%, NatureWorks 4032D raw material is used in the implementation process; modified thermoplastic starch 32wt%, self-made in this embodiment; compatibilizer 3.1wt%, Shandong Binzhou Jinsheng New Materials Technology Co., Ltd.'s ten polyglycerol ten stearate is used in the implementation process; calcium carbonate micropowder 15wt%, Hubei Tongji Furao Calcium Resources Development Co., Ltd.'s 1250 mesh food-grade calcium carbonate is used in the implementation process; each raw material is mixed according to the proportion, added into a high-speed mixer and mixed at 800rpm for 10min, and then transferred to a torque rheometer, the temperature is controlled at 170±5°C, and the mixing is carried out for 15min. The torque tends to be stable, the discharge is cooled and crushed to obtain a composite masterbatch.
[0047] Step S2: melt-extrude the composite masterbatch using an extruder, wherein the temperature zones during the melt extrusion process are set as: 160°C for zone one, 170°C for zone two, 185°C for zone three, 195°C for zone four, 200°C for zone five, and 185°C for zone six, and the die temperature is 200°C. After cooling, cut to obtain degradable and environmentally friendly straws.
[0048] Comparative Example 1
[0049] In this comparative example, cassava starch and polylactic acid are used to prepare degradable and environmentally friendly straws. The specific ingredients are: 53.5wt% polylactic acid, 4032D raw material from Nature Works is used in the implementation process; 28wt% cassava starch; 3.5wt% compatibilizer, polyglycerol decapristate from Shandong Binzhou Jinsheng New Materials Technology Co., Ltd. is used in the implementation process; 15wt% calcium carbonate powder, 1250 mesh food-grade calcium carbonate from Hubei Tongji Furao Calcium Resources Development Co., Ltd. is used in the implementation process; the specific process for preparing the straws is the same as that in Example 3.
[0050] Comparative Example 2
[0051] In this comparative example, commercially available thermoplastic starch and polylactic acid are used to prepare degradable and environmentally friendly straws. The specific ingredients are: 49.8wt% polylactic acid, 4032D raw material from Nature Works is used during the implementation process; 32wt% thermoplastic starch, YC200 raw material from Jiangyin Yuechuan Degradable Materials Co., Ltd.; 3.2wt% compatibilizer, polyglycerol decapristate from Shandong Binzhou Jinsheng New Materials Technology Co., Ltd. is used during the implementation process; 15wt% calcium carbonate powder, 1250 mesh food-grade calcium carbonate from Hubei Tongji Furao Calcium Resources Development Co., Ltd. is used during the implementation process; the specific process for preparing the straws is the same as that in Example 3.
[0052] The above molten extrudate was transferred into a mold, cooled and shaped under a pressure of 2.5 MPa, and a sample was obtained after demoulding. Samples were taken from the sample and the following tests were performed:
[0053] 1. Mechanical properties test: tensile test according to GB / T 1040.2-2022 standard, loading speed 10mm / min;
[0054] 2. Water resistance test: refer to GB / T 1034-2008 standard for water absorption test, use 23℃ deionized water as reagent, soak for 24h, drain for 30min and weigh to calculate water absorption rate, and dry and weigh the soaked sample, and calculate the weight loss rate by comparing with the original weighing data, which is recorded as water solubility;
[0055] 3. Biodegradability test: pre-embedding method was used to select humus soil from the same forest area, and the moisture content was adjusted to 30% and the temperature was 23°C. The samples were removed after 30 days, 60 days and 180 days of burial, and the impurities were removed and weighed. The weight loss rate was calculated and recorded as the degradation rate.
[0056] The specific test data are shown in the following table:
[0057] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Tensile strength / Mpa 36.2 30.9 34.7 18.5 22.4 Elongation at break / % 69.5 83.2 78.1 36.4 57.1 Water absorption / % 7.26 5.85 6.27 15.39 11.02 Water solubility / % 0.77 0.49 0.53 6.72 2.29 30d degradation rate / % 12.1 15.3 13.7 22.6 14.7 60d degradation rate / % 29.5 34.7 31.3 60.2 36.4 180d degradation rate / % 84.3 88.1 90.2 92.5 90.7
[0058] It can be seen from the test results in the above table that the straw material prepared in the embodiment has higher toughness than the comparative example, lower water absorption and water solubility, slowly degrades within 60 days, and rapidly degrades within 60-180 days, has good biodegradability, and is more stable in use.
[0059] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0060] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A degradable and environmentally friendly straw, characterized in that: The composition comprises, by weight percentage, 26-35 wt % of modified thermoplastic starch, 2.8-3.3 wt % of compatibilizer and 12-17 wt % of calcium carbonate powder, and the balance is polylactic acid; The modified thermoplastic starch is prepared by the following method: Step A1: premix acrylic anhydride and cyclohexane under dry nitrogen protection, add cassava starch and mix, heat to 50-60° C., stir and react for 2.5-3 hours, add ammonia water for washing after the reaction, let stand and precipitate to remove the liquid phase, and then vacuum dry to obtain olefinated starch; Step A2: Mix epoxidized soybean oil, chitosan quaternary ammonium salt and ethyl acetate, control the temperature in a water bath to be 30-40° C., stir and slowly add mercaptoethylamine, control the total reaction time of mercaptoethylamine addition to be 4-5 h, and after the reaction is completed, vacuum dry to remove ethyl acetate to obtain a modifier; Step A3: the olefinated starch, the modifier and ethanol are mixed, and the mixture is subjected to gamma irradiation treatment, and the irradiation dose is controlled to be 80-100 kGy. After the irradiation, the ethanol is removed by vacuum drying to obtain a modified thermoplastic starch.
2. The degradable and environmentally friendly straw according to claim 1, characterized in that: The usage ratio of cassava starch, acrylic anhydride and cyclohexane is 50g:60-80mmol:55-70mL.
3. The degradable and environmentally friendly straw according to claim 2, characterized in that: The usage ratio of the epoxidation amount of epoxidized soybean oil, mercaptoethylamine, chitosan quaternary ammonium salt and ethyl acetate is 0.1 mol: 70-80 mmol: 20-25 mg: 120-150 mL.
4. The degradable and environmentally friendly straw according to claim 3, characterized in that: The usage ratio of olefinic starch, modifier and ethanol is 50g:4.2-5.5g:65-75mL.
5. The degradable and environmentally friendly straw according to claim 4, characterized in that: The gamma irradiation source is Co-60, and the irradiation dose rate is 150-200Gy / min.
6. The degradable and environmentally friendly straw according to claim 1, characterized in that: The compatibilizer is polyglyceryl stearate.
7. The method for preparing a degradable and environmentally friendly straw according to claim 1, characterized in that: The steps include: Step S1: Mix the raw materials according to the proportion, mix them evenly with a high-speed mixer, add them into a torque rheometer for internal kneading and blending, cool and crush the discharged materials to obtain a composite masterbatch; Step S2: melt-extrude the composite masterbatch using an extruder, and cut it after cooling to obtain a degradable and environmentally friendly straw.
8. The method for preparing a degradable and environmentally friendly straw according to claim 7, characterized in that: The temperature of internal mixing is 170±5°C; the temperature zones in the melt extrusion process are set as: zone 1 155-170°C, zone 2 165-180°C, zone 3 180-195°C, zone 4 185-195°C, zone 5 190-200°C, zone 6 180-190°C, and the die temperature is 190-200°C.
Citation Information
Patent Citations
All-degradable thermoplastic starch / polylactic acid blend material and preparation method thereof
CN103159984A
High toughness and high strength starch composite material and preparation method
CN107513258A